Геологічні пам’ятки України: динаміка змін та перспективи збереження - Нікітіна, А.О. (Інститут геологічних наук НАН України, 2009)
Рассмотрена динамика изменений в состоянии геологических памятников на Украине, а также подходы к их охране и использованию в туризме. Dynamic of changes in the state of geosites of Ukraine is under consideration. The approach to conservation and exploitation them in tourism are presented.